Search for an Image of Peacetime in the American Culture of the 1970s–1980s - Sysolyatin, Anton A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2024)
This article discusses the search of an image of peacetime in the USA culture in the 1970s–1980s after the Vietnam War represented in the public debate between institutional and counter-institutional parties. The article focuses on the attempts to find a language of new forms of civil accord in the ambiguous sociopolitical situation, when it was unclear which institution was capable of formulating conclusive results of war conflict and its consequences for American culture. The conceptual basis of the analysis consists in the distinction between institutes and counter-institutes developed by philosopher P. Bojanic. The key element of that distinction is the idea of fair violence. Institutions establish civil order and accord on the basis of an idea of justice, whereas counter-institutes make it possible to incorporate any alternative viewpoints into the common institutional forms of life. The author demonstrates that public institutions of the USA in the period in question were concentrated on the rehabilitation of their state and military prestige within the country. The government criticised the conception of the Vietnam syndrome and conducted a policy of heroisation of Vietnam veterans in order to enable themselves to use military troops in future war campaigns. In the case of counter-institutes, the author points out the tendency to self-separation from institutional processes regarding state and civil society. The texts of “trench prose” about the Vietnam War act as significant evidence of the lack of articulated demand for consolidation and restoration of civic unity on the part of counter-institutions. As a result, the analysis helps establish that both parts of public debate concerning the consequences of the Vietnam War were not interested in re-evaluating their baseline idea of justice. For American culture in the 1970s and 1980s, this meant that the under-reflected experience of war violence remained its vulnerable side, preventing it from constructing effective projects of peaceful life.